Evaluation method of filling difficulty for profile ring rolling cavity based on FEM and RSM - HU Yang; LIU Dong; YANG Yanhui; WANG Jianguo; LYU Nan; RAO Haodong (Xibei Gongye Daxue Xuebao, 2023)
During the rolling process of profile ring, the design of the rolling cavity directly affects the forming quality of the final ring. In order to improve the cavity filling rate and reduce the production cycle time, this paper proposes a general evaluation method of the filling difficulty for profile ring rolling cavity by combining the response surface method(RSM) and the finite element method(FEM) with the step-type ring as the research object. Firstly, a universally applicable design method for profile ring rolling cavity is proposed, and based on the description of the rolling cavity, three design variables and a corresponding response objective are defined to achieve multi-objective optimization. Secondly, a finite element model of this step-type ring rolling process is established, and the response model is built and improved by significance analysis and analysis of variance(ANOVA) based on the forming simulation results. Then, the effects of different variables on the optimization objectives are comprehensively investigated by this response model. Finally, the evaluation method of the filling difficulty for profile ring rolling cavity is obtained by combining the contour plot of the response objective.